2013
DOI: 10.4103/2277-9175.115803
|View full text |Cite
|
Sign up to set email alerts
|

Study of the prevalence of azoospermia in patients with Hodgkin′s lymphoma prior to treatment

Abstract: Background:Infertility is one of the main problems of patients with Hodgkin's lymphoma, as this causes specific effects in the social, family, and emotional life of patients. Hodgkin's lymphoma is a neoplastic disorder that comprises of 0.6% of all cancers and often occurs in middle-aged people, with a mean age of 26 years. It originates from neoplastic changes in the lymphoid cells, which lead to different complications in the body organs. One important complication of Hodgkin's lymphoma is humoral and cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Lifestyle tends to influence the quality of sperm cell production, with obesity, smoking, poor diet, lack of exercise, and STIs being risk factors associated with male infertility worldwide. 96 A previous study by Taleb et al 97 showed that 10% of the patients had azoospermia, which was clear in its progressive stages. This was similar to the proportion we reported in our study findings.…”
Section: Laboratory Characterisation Of Seminal Abnormalitiesmentioning
confidence: 94%
“…Lifestyle tends to influence the quality of sperm cell production, with obesity, smoking, poor diet, lack of exercise, and STIs being risk factors associated with male infertility worldwide. 96 A previous study by Taleb et al 97 showed that 10% of the patients had azoospermia, which was clear in its progressive stages. This was similar to the proportion we reported in our study findings.…”
Section: Laboratory Characterisation Of Seminal Abnormalitiesmentioning
confidence: 94%